2015
DOI: 10.1039/c4ay02450h
|View full text |Cite
|
Sign up to set email alerts
|

New voltammetric analysis of olanzapine in tablets and human urine samples using a modified carbon paste sensor electrode incorporating gold nanoparticles and glutamine in a micellar medium

Abstract: An effective novel electrochemical sensor for selective determination of olanzapine (OLA) was introduced. The prepared sensor was based on carbon paste electrode chemically modified with glutamine (GL) and gold nanoparticles (GN) in presence of sodium dodecyl sulphate (SDS) in the medium. The effect of carbon paste composition and scan rate were tested. Working solution pH was 7 . The analytical method validation parameters were studied. The linear response was obtained for OLA in the ranges of 5×10 −7 to 1.25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The presence of ascorbic acid (ASA) and uric acid (UA) were also explored upon the electrochemical oxidation of DPX ( Figure S6 ) because these two analytes coexist in many biological samples. 50 The electrochemical oxidation of 6.5 × 10 –6 M DPX in the presence of 6.5 × 10 –6 M ASA and UA were investigated using the Cs–Au/SPE via SWV, as shown in Figure S6 , which demonstrates that these are far resolved from the analytical peak of interest. The effect of many substances that can potentially interfere with the electroanalytical determination of DPX were also examined.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The presence of ascorbic acid (ASA) and uric acid (UA) were also explored upon the electrochemical oxidation of DPX ( Figure S6 ) because these two analytes coexist in many biological samples. 50 The electrochemical oxidation of 6.5 × 10 –6 M DPX in the presence of 6.5 × 10 –6 M ASA and UA were investigated using the Cs–Au/SPE via SWV, as shown in Figure S6 , which demonstrates that these are far resolved from the analytical peak of interest. The effect of many substances that can potentially interfere with the electroanalytical determination of DPX were also examined.…”
Section: Results and Discussionmentioning
confidence: 99%
“…There are also electroanalytical techniques such as potentiometry (Rouhani & Soleymanpour, 2019), amperometry with HPLC (Raggi et al, 2000), and voltammetry. Voltammetric methods are used for the determination of many antipsychotics including olanzapine (Karadurmus et al, 2019;Kul, 2019), the oxidative behavior of olanzapine with modified electrodes (Azab & Amany, 2019;Behzad et al, 2016;Ahmed et al, 2015;Shahrokhian et al, 2014;El Shal, 2013;Mashhadizadeh & Afshar, 2012;Merli et al, 2012), and the oxidative behavior of olanzapine on a glassy carbon electrode (Yılmaz et al, 2017;Biryol & Erk, 2013). However, an electroreduction study of olanzapine has not yet been reported.…”
Section: ___________________mentioning
confidence: 99%
“…As a result, pH 5.0 was selected for this study. Ahmed et al demonstrated OLZ detection with a modified carbon paste sensor electrode incorporating gold nanoparticles and glutamine in a micellar medium (Ahmed et al 2015). They reported an LOD value of 3.58 × 10 -9 M in Britton-Robinson buffer (pH 7.0) and demonstrated the recovery of OLZ in urine samples.…”
Section: Introductionmentioning
confidence: 99%